2020
DOI: 10.1111/bju.15197
|View full text |Cite
|
Sign up to set email alerts
|

Artificial urinary sphincter significantly better than fixed sling for moderate post‐prostatectomy stress urinary incontinence: a propensity score‐matched study

Abstract: Objective To compare the efficacy of artificial urinary sphincter (AUS) vs retrourethral transobturator sling (RTS) in men with moderate post‐prostatectomy urinary incontinence (PPI) using propensity score‐matching analysis to enhance the validity of the comparison (Canadian Task Force classification II‐2). Patients and methods Consecutive men with moderate (3–5 pads/day) stress‐prevalent PPI were included if implanted with a RTS (TiLOOP® Male; pfm medical, Köln, Germany) or AUS (AMS800®; Boston Scientific, Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Considering the inclusion and exclusion criteria for the study, 520 articles were screened and 303 full-texts were assessed carefully for eligibility. Finally, 5 eligible articles were selected in meta-analysis ( 7 9 , 14 , 15 ). The flow diagram of articles selection was described in Supplementary Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the inclusion and exclusion criteria for the study, 520 articles were screened and 303 full-texts were assessed carefully for eligibility. Finally, 5 eligible articles were selected in meta-analysis ( 7 9 , 14 , 15 ). The flow diagram of articles selection was described in Supplementary Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The assessment outcomes showed that most articles were well-designed and had little risk of bias. The included patients in each study differed slightly, some based on moderate daily pad use ( 9 , 14 , 15 ), while some based on moderate scale score ( 8 ). Outcome variabilities measured in studies were also found, most defining surgical success as 0–1 pad/d postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the quality of scientific evidences supporting the use of this device is low, characterized by heterogenous data, low quality study, and lack of validated outcomes [15]. Additionally, comparative studies of the AUS versus other surgical devices are rare [16, 17]. A recent propensity score-matched analysis showed better results for the AUS than for the fixed sling for moderate SUI.…”
Section: Discussionmentioning
confidence: 99%